Targeting the nucleic acid oxidative damage repair enzyme MTH1: a promising therapeutic option - Ding, Yifeng; Liu, Qingquan (Frontiers in Cell and Developmental Biology, 2024)
As the population grows and ages and with the increasing number of poor lifestyle habits, the incidence of disease and mortality increases. Although the disease is currently being treated through various diagnostic and therapeutic techniques, drug side effects and drug resistance can seriously affect the effectiveness of treatment. This reduces the quality of life of patients. In order to improve the treatability of patients' diseases, researchers are constantly exploring feasible therapeutic targets. MTH 1 (mut T homolog1) is the homologous enzyme of Mut T. It is a nucleotide pyrophosphatase, which is mainly involved in the DNA damage repair process by preventing oxidative damage of deoxyribonucleoside triphosphates (dNTPs) doped into DNA replication, resulting in base mismatches. Several studies have shown that MTH1 plays a key role in a variety of diseases, especially antitumor, and is expected to be a new target for antitumor drugs. This article outlines the structural features and biological functions of MTH1, its research progress in a variety of diseases and tumors, and the therapeutic options against MTH1. Providing new targets for antitumor therapeutic regimens, research against MTH1 is expected to be an inherently promising research direction.